Impacts of climate smart agriculture on livelihoods in sub-Saharan Africa: A meta-analysis - Simutowe, Esau; Ngoma, Hambulo; Thierfelder, Christian (SAGE Publications, 2025)
Sub-Saharan Africa is grappling with increasing food demand amid a growing population amidst a surging climate crisis. Climate Smart Agriculture (CSA) emerges as one option to address these challenges and enhance livelihoods. However, evidence of the impacts of CSA on livelihoods remains thin and mixed. We used a meta-analysis with 19 studies to assess the impacts of CSA practices on crop and household income, poverty, and food security in sub-Saharan Africa. Based on the literature, adoption of CSA is positively correlated with crop and household income, and food security. We do not find statistically significant effects on poverty and food security results. These results signify the need to integrate CSA with other complementary measures such as access to extension services, markets, climate-related risk insurance, and finance to improve food security and reduce poverty. We can conjecture that the positive effects on incomes are not sufficient to significantly drive up food security and poverty alleviation.